The Origin of North Mesopotamian Arabic - Hakam Muhammed Ghanim Hakam Muhammed Ghanim (مجلة النور للدراسات الانسانية)
This research paper explores the origin and distinct characteristics of the Noarth Mesopotamian Arabic dialect, specifically the Moslawi dialect spoken in Mosul, northern Iraq. The study begins with tracing the roots of the Arabic language within the Semitic language family tree and examines the emergence of Modern Arabic Dialects. It highlights Ferguson's theory that these dialects originated from a asimplified Koine as the most plausible explanation. The paper then delves into the Mesopotamian dialect group, detailing the division into qeltu and gelet varieties through bedouinization. The phonological and lexical uniqueness of Moslawi is analyzed, emphasizing the persistent use of the phoneme /q/ by Moslawi speakers and the systematic vowel-raising rule that differentiates it from other dialects. Extensive language contact, with Persian, Turkish, Hindi, Kurdish, and English, is also discussed, which explains the numerous borrowed words in Moslawi. This research underscores the complex historical and sociolinguistic factors contributing to the distinctiveness of the Moslawi dialect within the broader context of Arabic dialects.